2016
DOI: 10.1051/hydro/2016001
|View full text |Cite
|
Sign up to set email alerts
|

Nam Theun 2 Reservoir four years after commissioning: significance of drawdown methane emissions and other pathways

Abstract: -Hydro-reservoirs are recognized as potentially significant emitters of methane at the global scale. However, there are still large uncertainties in estimating such emissions at this scale due to the lack of comprehensive measurements of methane emissions in a wide range of climatic zones, for hydro-reservoirs with variable characteristics, and including all emissions pathways. This study presents an assessment of methane emissions for the 2013 year, that is four years after commissioning, for the Nam Theun 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…Our estimated gross emissions are likely to be higher than net emissions, but the inclusion of emissions from degassing would have increased our emission estimates, as it was only partially considered in our models (not all measurements underlying the regression models included CH 4 bubbles). For example, in the case of two tropical reservoirs, Balbina and Petit Saut, the degassing of CH 4 is considered to account for 35% and 60% of the total CH 4 emissions, respectively (Demarty and Bastien 2011), and in Nam Theun 2 reservoir the gross emissions were estimated to be 23%-27% larger than the net emissions (Deshmukh et al 2014, Serça et al 2016, Deshmukh et al 2016.…”
Section: Limitations and Ways Forwardmentioning
confidence: 99%
“…Our estimated gross emissions are likely to be higher than net emissions, but the inclusion of emissions from degassing would have increased our emission estimates, as it was only partially considered in our models (not all measurements underlying the regression models included CH 4 bubbles). For example, in the case of two tropical reservoirs, Balbina and Petit Saut, the degassing of CH 4 is considered to account for 35% and 60% of the total CH 4 emissions, respectively (Demarty and Bastien 2011), and in Nam Theun 2 reservoir the gross emissions were estimated to be 23%-27% larger than the net emissions (Deshmukh et al 2014, Serça et al 2016, Deshmukh et al 2016.…”
Section: Limitations and Ways Forwardmentioning
confidence: 99%
“…Although previous studies have shown that GHG emissions strongly fluctuate during a drying and rewetting cycle (e.g. Yang et al 2012;Gallo et al 2014;Serça et al 2016), most assessments are based on infrequent measurements, varying from once a year along a transect (Serça et al 2016) to twice a month at specific locations (Yang et al 2012). As pulsed fluxes may be critical for the total GHG emissions, especially during a period of rewetting (Gallo et al 2014), infrequent measurements are likely to result in an underestimation of overall emissions.…”
Section: Introductionmentioning
confidence: 99%
“…This is a transbasin hydroelectric reservoir that diverts water from the Nam Theun River (a Mekong tributary) to the Xe Bangfai River (another Mekong tributary). The reservoir was described in detail in Descloux et al (), and the carbon cycle and especially the greenhouse gas emissions were monitored since impoundment (Chanudet, Guédant, et al, ; Chanudet, Smits, et al, ; Deshmukh et al, , ; Guérin et al, ; Serça et al, ). The reservoir surface fluctuated from 140 km 2 (525.5 m above sea level) to around 490 km 2 at the full water level (538 m above sea level) between 2009 and 2013.…”
Section: Methodsmentioning
confidence: 99%